Monitoring heterogeneity and carbon sequestration of restored river-wetland corridors - Hinshaw, Sarah Kathleen, author; Wohl, Ellen, advisor; Rathburn, Sara, committee member; Morrison, Ryan, committee member; McGrath, Dan, committee member (Colorado State University. Libraries, 2022)
Innovation of new stream restoration strategies over the past three decades has added much-needed geomorphic complexity and ecological consideration to the practice of stream restoration. With the modernization of stream restoration to include biologically driven feedbacks, methods in monitoring must be simultaneously created to match the current progress. In addition, modern stream restoration practices offer significant opportunity to store carbon in restored river-wetland corridors by increasing carbon sequestration potential of the affected landscapes via rewetting valley bottoms and enhancing fluvial deposition. To address the need for monitoring techniques that capture complex river corridor restoration and carbon sequestration, I present in this dissertation: 1) the development of a geomorphic monitoring strategy that is applied to a valley-scale floodplain enhancement project that involved regrading of the valley bottom and abundant large wood placement, 2) a conceptual framework and protocol for estimating carbon sequestration potential in restored river-wetland corridors, and 3) the application of the latter protocol across multiple restoration projects in the western USA. With the monitoring protocol, which is based on plots rather than river cross-sections, I found finer substrate grain sizes, reduced canopy cover, spatial patterns in particulate organic matter, and the initial signatures of expected changes in heterogeneity at the valley-scale floodplain enhancement project over two years after project implementation. In the context of carbon sequestration among eight sites combined, I found the majority of pre-restoration or degraded condition sites to have significantly fewer carbon stocks than restoration projects or reference conditions, and the highest carbon stocks in reference condition sites. The chapters of this dissertation are not only intended to provide context and methods to measure stream restoration projects, but also to examine the state and trends of stream restoration in general and to contribute to the understanding of rivers in the global carbon cycle.
Keywords: fluvial; process-based restoration; stage 0; monitoring; carbon; river restoration